Selective internal radiation therapy with 90Y-SIR-Spheres microspheres for non-resectable colorectal metastases in the liver. (17th May 2011) - Hadaki, M; Praseedom, R; Brais, R; See, T C; Balan, K; Wilson, C B
Abstract : Almost half the patients with colorectal cancer will develop liver metastasis at some stage during their disease. Potentially curative surgical resection is possible in some of these patients. In those patients unsuitable for surgery, treatment with systemic chemotherapy and external radiation therapy is relatively ineffective. Many studies have described the successful use of selective internal radiation therapy (SIRT) with 90Y-SIR-Spheres microspheres in patients with inoperable liver metastasis. The authors report on a patient who has been in complete remission for 1 year after treatment with SIRT.